Immediate effect of the finger kazoo technique on patients with laryngeal disorders: case study (Research, Society and Development, 2020)
Purpouse: To verify the perceptual-auditory vocal changes after the finger kazoo vocal technique in three women with laryngeal affections. Methods: Three adult women with the respective medical diagnosis of: sulcus vocalis in the stria major (S1), vocal nodules (S2), and laryngeal microweb (S3) performed three sets of 15 repetitions of the finger kazoo with 30 s of passive rest between sets. Two judges performed the perceptual-auditory vocal analysis before, immediately after therapy, and five minutes after absolute silence. Results: Breathiness, asthenia and instability decreased immediately after the execution of the finger kazoo in S1 and S3 and breathiness and instability decreased in S2. After five minutes of silence, all parameters decreased, except the strain in S1; hoarseness, breathiness and instability decreased in S2; and all parameters, except the strain, worsened in S3. Conclusion: The finger kazoo performed in a session of three series of 15 repetitions caused an improvement in perceptual-auditory parameters in the three women with laryngeal affections in both moments after therapy, except for the patient with laryngeal microweb who showed improvement immediately after the technique and worsened afterwards five minutes of silence.